Obytný komplex s provozovnou - Severa, Aleš (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Diplomová práce se zabývá dispozičním, konstrukčním, požárním a tepelně technickým řešením bytového komplexu s provozovnou. Komplex je rozdělen do čtyř funkčních částí a to do podzemních garáží, administrativní, provozní a bytové. Tento navrhovaný objekt má čtyři nadzemní podlaží a jedno podzemní. Poslední podlaží je zastřešeno plochou střechou. Konstrukční systém je železobetonový sloupový a stěnový v prvních dvou podlažích dále přechází ve zděný stěnový. Stropní konstrukce je monolitická železobetonová stropní deska křížem pnutá.

This thesis deals with the layout, construction, fire and thermal technical solution for residential building with business part. The residential complex is divided into four functional parts - underground garages, administrative, operational and residential part. This proposed building has four floors and a basement. The upper floor is sheltered by a flat roof. The constructional system is made of reinforced concrete columns and walls in the first two floors, as for the next floors the brick wall construction is used. The ceiling construction is a monolithic reinforced concrete panel with cross tension.
Residential buiding with bussines part
Keywords: Bytový komplex s provozovnou; železobeton; monolitická konstrukce; sloup; stěna; podlaží; Residential complex with business premises; reinforced concrete; monolithic construction; column; wall; floor